1993
DOI: 10.1212/wnl.43.9.1779
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prevalence of myasthenia gravis in western Denmark

Abstract: We studied the epidemiology of myasthenia gravis (MG) in western Denmark from 1975 to 1989, basing case identification on records from all hospitals in the survey area. The population surveyed was 2.80 million in 1985. The average annual incidence rate was 5.0 per million population (women, 5.9; men, 4.2). The point-prevalence rate (January 1, 1990) was 78 per million population (women, 102; men, 53). In men, the incidence increased after 40 years. In women, the incidence rates showed a bimodal pattern with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
41
4
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 0 publications
9
41
4
1
Order By: Relevance
“…According to the Osserman and Genkins classification, patients were categorized into all groups at first assessment, with the majority in group IIa. 18 Coincident with Christensen et al, 43% of the patients were into this group 19 . At final neurological examination, 63.8% of all patients were asymptomatic and none were in group III or IV.…”
Section: Clinical Presentationmentioning
confidence: 65%
See 1 more Smart Citation
“…According to the Osserman and Genkins classification, patients were categorized into all groups at first assessment, with the majority in group IIa. 18 Coincident with Christensen et al, 43% of the patients were into this group 19 . At final neurological examination, 63.8% of all patients were asymptomatic and none were in group III or IV.…”
Section: Clinical Presentationmentioning
confidence: 65%
“…These data are similar to those reported by Cunha et al who found a single peak age of onset in males between 20 and 35 years old (44.8%) and in females between 15 and 30 years old (45.2%) 5 . Christensen et al found a greater incidence in men older than 40 years, but demonstrated a bimodal pattern with one peak consisting of females at child-bearing age and a second peak of older women 19 . Conversely, Singhal et al, in India, studied 836 patients and showed male preponderance with a ratio of 2.7:1 and a single (later) peak of males in the sixth and seventh decades 3 .…”
Section: General Socio-demographic Findingsmentioning
confidence: 99%
“…MG has a prevalence of 20-400 per million based on large population studies, and OM comprises approximately 20% of all cases (Somnier et al 1991;Phillips et al 1992;Christensen et al 1993;Phillips and Torner 1996;MacDonald et al 2000;Casetta et al 2010). The classic statement of the disease being of old men and young woman is true with an age distribution being bimodal with incidence peaks in the 20's for women and 40's for men (Phillips and Torner 1996;Grob 1999;Mantegazza et al 2003;Matsuda et al 2005).…”
Section: Epidemiologymentioning
confidence: 99%
“…Although MG can develop at any age, two peaks have been recognized in its incidence: the twenties in women and, less consistently, the over-fifties in men (2,3). In recent decades, however, several reports have noted that the incidence of elderly-onset MG has been increasing in the United States and European countries (3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%